On Stability of Solutions of a Stochastic Equation - Dorogovtsev, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We present conditions for the stability of stationary solutions of an abstract linear stochastic differential equation with respect to the coefficient of the leading derivative.